2014
DOI: 10.1371/journal.pone.0113835
|View full text |Cite
|
Sign up to set email alerts
|

The Cpn10(1) Co-Chaperonin of A. thaliana Functions Only as a Hetero-Oligomer with Cpn20

Abstract: The A. thaliana genome encodes five co-chaperonin homologs, three of which are destined to the chloroplast. Two of the proteins, Cpn10(2) and Cpn20, form functional homo-oligomers in vitro. In the current work, we present data on the structure and function of the third A. thaliana co-chaperonin, which exhibits unique properties. We found that purified recombinant Cpn10(1) forms inactive dimers in solution, in contrast to the active heptamers that are formed by canonical Cpn10s. Additionally, our data demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that hetero‐oligomers consisting of Cpn10 and Cpn20 occur frequently in vitro , which raised the question whether such hetero‐oligomers also represent functional co‐chaperonins in vivo (Tsai et al ., ; Vitlin Gruber et al ., ). To confirm the existence of chloroplast co‐chaperonin hetero‐oligomers in vivo , we carried out co‐immunoprecipitation assays from Chlamydomonas chloroplast stroma and total protein using an antiserum against CPN20.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown that hetero‐oligomers consisting of Cpn10 and Cpn20 occur frequently in vitro , which raised the question whether such hetero‐oligomers also represent functional co‐chaperonins in vivo (Tsai et al ., ; Vitlin Gruber et al ., ). To confirm the existence of chloroplast co‐chaperonin hetero‐oligomers in vivo , we carried out co‐immunoprecipitation assays from Chlamydomonas chloroplast stroma and total protein using an antiserum against CPN20.…”
Section: Resultsmentioning
confidence: 97%
“…Chloroplast co‐chaperonin subunits are also divided into two subtypes, the conventional ~10‐kDa GroES‐like Cpn10 and the ~20‐kDa Cpn20, which consists of two tandem Cpn10 domains joined head to tail (Musgrove et al ., ; Bertsch et al ., ; Baneyx et al ., ). Both chloroplast chaperonin and co‐chaperonin complexes are liable to exist as intricate hetero‐oligomers, although Cpn60β and Cpn20 homo‐oligomers have been shown to be functional in vitro (Viitanen et al ., ; Dickson et al ., ; Tsai et al ., ; Vitlin Gruber et al ., ; Bai et al ., ). Another unique aspect of the chloroplast chaperonin system compared with its bacterial and mitochondrial counterparts is the capability to assist in the folding and assembly of ribulose 1,5‐bisphosphate carboxylase/oxygenase (Rubisco), which accounts for ~30–50% of soluble proteins in chloroplasts (Barraclough and Ellis, ; Dhingra et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“… reported that none of the three individual cochaperonin (CrCPN11, CrCPN20 and CrCPN23) of Chlamydomonas was functionally active, although hetero‐oligomers consisting of seven 10‐kDa domains cooperated with chaperonin in refolding model substrates. By contrast, in Arabidopsis , both homo‐oligomers of Cpn10(2) and Cpn20 were functional as cochaperonins , whereas Cpn10(1) was incorporated into Cpn20 oligomers to cooperate with chaperonin . In the present study, we investigated the cooperation of various cochaperonins with the homo‐oligomeric GroEL and hetero‐oligomeric CrCPN60 chaperonins.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, Vitlin Gruber et al . found that, in contrast to AtCpn10(2), which forms heptamers interacting with chaperonin as cofactors, Arabidopsis AtCpn10(1) was not functional unless in the hetero‐oligomeric form with AtCpn20. Moreover, AtCpn20 is postulated to play multiple functions in chloroplasts independent of its co‐chaperonin role in Arabidopsis (e.g.…”
Section: Introductionmentioning
confidence: 98%